Poems of Goethe : A Sequel to "Goethe, the Lyrist" - Zeydel, Edwin H. (Chapel Hill The University of North Carolina Press, 1957)
Following his previous translation of one hundred of Goethe's poems, in this volume Zeydel presents translations of a selection of Goethe's shorter poems, the majority of which were written in the last twenty years of his life. The translator gives careful attention to details of substance, form and style, and to the spirit of the original, reproducing the simplicity and naturalness of language so characteristic of Goethe. The original text in German appears on facing pages.
National Endowment for the Humanities
Andrew W. Mellon Foundation
English
German
Keywords: Poetry; Poetry; German Studies; Literature